Halal Food Market Segmentation in New Zealand: New Opportunities for Indonesian Halal Food: A Systematic Literature Review (SLR) - Muhammad Luthfi Attaka Rizqi; Faza Muhlizoh A. Noer; Lissa Rosdiana Noer (Halal Research, 2025)
The halal food market in New Zealand is experiencing rapid growth, driven by a growing Muslim population and increasing awareness of the halal lifestyle. Indonesia's halal food industry has a great opportunity to capitalize on this lucrative market by understanding market characteristics, conducting effective market segmentation, and developing appropriate marketing strategies. Key findings show that the halal food market in New Zealand is divided into several segments based on factors such as demographics, lifestyle, and values. These segments have different needs and preferences for halal food products. The research also shows that Indonesia's halal food industry has several competitive advantages that can help it penetrate the New Zealand market. These advantages include high product quality, wide varieties, and competitive pricing. The journal concludes that Indonesia's halal food industry has a great opportunity to thrive in the New Zealand market. By implementing the right strategies, the Indonesian halal food industry can increase its market share in New Zealand and its profits. This article aims to conduct a systematic literature review of research on halal food market segmentation in New Zealand. The review aims to identify key market segments, their characteristics, and the implications for Indonesia's halal food industry.